CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL): AN EXPERIMENTAL STUDY ON CLIL COMPATIBILITY WITH THE MODERN GREEK EDUCATIONAL SYSTEM - Catherine Georgopoulou Theodosiou (University of Kuningan, 2016)
This paper focuses on the Content and Language Integrated Learning (CLIL) method for (foreign) language teaching. The CLIL approach is rapidly gaining momentum across Europe and all over the world. It is the result of recent European Union efforts to develop and apply innovative educational practices of interdisciplinary character in order to bridge the gap between foreign language education and optimum learning outcomes. In order to investigate the compatibility of CLIL with the contemporary Greek educational reality, a small-scale experimental research study was set up, including the development of original e-learning material, a pilot class instruction based on this material and the evaluation of the results. The class instruction was based on Project-Based Learning whereas Collaborative Learning was supported by the Edmodo e-learning platform. Information on the progress of the pilot class instruction and the learning outcomes achieved was disseminated through a wiki set up for this task.Keywords: CLIL, interdisciplinarity, plurilingualism, multiculturalism, assessment, Information and Communication Technology (ICT)